El contrato de representación comercial : Åla nueva agencia comercial? (2016)
The reform of the contract of commercial agency of goods that is currently processed in the Congress of the Republic, is one of the commitments that Colombia acquired after the negotiation of the Agreement of Trade Promotion with the United States in the year 2012. Mainly, Legislative Project 146 of 2015 - Camara de representantes seeks to eliminate the commercial compensation that must be paid to the agent at the end of the contract and the presumption of exclusivity of territory in favor of the agent, rules that would undoubtedly establish a regime more beneficial to the agent in relation to the one In the current legislation. However, in parallel to Congress, Legislative Bill 243 of 2015-Camara, 154 of 2015 - Senate is also being processed: "By means of which commercial representation is defined and mechanisms of protection are established for representatives of traders and agents in the territory national". This new institution may become confused with the commercial agency, given the similarity of its characteristics, elements and economic function. In addition, this bill, if approved in the Senate, would have an effect different from that pursued by the draft amendment of the commercial property agency: it would revive the benefit for the termination of the contract and the presumption of exclusivity would be reborn, Indemnity rather onerous in favor of the representative in case of termination without just cause by the foreign house. The purpose of this study is to analyze the implications of the coexistence of these two projects, if they are approved in the Colombian legal system and in a timely manner if the inclusion of the contract of representation of foreign house in the current context is justified. To do this, a basic review of the commercial agency as a distribution contract, and a critical comparative examination of the bills referred to above, will be made through a descriptive and dogmatic methodology.